2021
DOI: 10.1002/jcb.29903
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of geranylgeranylacetone and amelogenin promotes angiogenesis and wound healing in human periodontal ligament cells

Abstract: Amelogenin directly binds to glucose‐regulated protein 78 (Grp78). Cell migration activity is expected to increase when human periodontal ligament cells (hPDLCs) overexpressing Grp78 are treated with amelogenin. Geranylgeranylacetone (GGA) is a drug that induces the expression of heat shock protein and is routinely used to treat gastric ulcers. Here, we investigated the changes in the properties and behavior of hPDLCs in response to treatment with GGA and the synergistic effects of amelogenin stimulation in hP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Liu et al 22 found that 2 transcripts of FBXO5 (transcripts a and b) promoted migration of hPDLSCs and then facilitated periodontal tissue regeneration. Yamato et al 23 indicated that geranylgeranylacetone treatment increased the expression of GRP78 protein in hPDLCs, and GRP78 could induce the migration of hPDLCs to the root surface and release cytokines involved in tissue repair, thus promoting wound healing. In our study, wound healing and transwell assays confirmed that migratory capacity of hPDLCs was significantly suppressed after overexpression of MZB1, while knockdown of MZB1 performed the opposite way, suggesting the negative role of MZB1 in periodontal tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 22 found that 2 transcripts of FBXO5 (transcripts a and b) promoted migration of hPDLSCs and then facilitated periodontal tissue regeneration. Yamato et al 23 indicated that geranylgeranylacetone treatment increased the expression of GRP78 protein in hPDLCs, and GRP78 could induce the migration of hPDLCs to the root surface and release cytokines involved in tissue repair, thus promoting wound healing. In our study, wound healing and transwell assays confirmed that migratory capacity of hPDLCs was significantly suppressed after overexpression of MZB1, while knockdown of MZB1 performed the opposite way, suggesting the negative role of MZB1 in periodontal tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, hPDLCs play an important role in mechanosensing and mechanotransduction (Sun et al, 2021). Since the periodontal ligament is adjacent to the alveolar bone, the biological activity of periodontal ligament cells is likely to affect the metabolism of alveolar bone (Yamato et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They were treated with media containing 5 mM PMA (positive control), normal media (negative control), or reserved conditioned media from cells encapsulated in gels with varying concentrations of NETs (Section 5.2.9). An IL-8 neutralizing antibody previously used by Yamato et al [46] (15 µg/mL, AHC0881, Thermofisher) was added to half the wells.…”
Section: Methodsmentioning
confidence: 99%
“…They were treated with media containing 5 mM PMA (positive control), normal media (negative control), or reserved conditioned media from cells encapsulated in gels with varying concentrations of NETs (Section 5.2.9). An IL-8 neutralizing antibody previously used by Yamato et al [46] (15 µg/mL, AHC0881, Thermofisher) was added to half the wells. After 3 hr, the media was collected and stored at -80 o C for later analysis, and cells were fixed in 4% paraformaldehyde (Electron Microscopy Services) for 15 min at room temperature.…”
Section: Conditioned Media Netosis Studymentioning
confidence: 99%